Socioeconomic and contextual determinants of biopesticide adoption among Indonesian farmers - ISTRININGSIH ISTRININGSIH; ASTRINA YULIANTI; YOVITA ANGGITA DEWI; VYTA WAHYU HANIFAH; ANGGITA TRESLIYANA SURYANA; RIESTI TRIYANTI; EKA TRIANA YUNIARSIH; ALFAYANTI ALFAYANTI; DADANG DADANG; RIZKA AMALIA NUGRAHAPSARI (Smujo International, 2026)
Abstract. Istriningsih, Yulianti A, Dewi YA, Hanifah VW, Suryana AT, Triyanti R, Yuniarsih ET, Alfayanti, Dadang, Nugrahapsari RA. 2026. Socioeconomic and contextual determinants of biopesticide adoption among Indonesian farmers. Asian J Agric 10 (1): g100176. https://doi.org/10.13057/asianjagric/g100176. Despite being more environmentally friendly than synthetic pesticides, biopesticides remain underutilized in Indonesia due to socioeconomic and contextual constraints affecting farmers’ adoption decisions. This study employs a Theory of Planned Behavior (TPB)-informed background factor framework to examine the socioeconomic and contextual determinants of biopesticide adoption using survey data from 322 farmers cultivating six major crops across five Indonesian provinces between August and December 2020 and applies a logit regression model. The results indicate that participation in training programs, family size, formal education, and farming experience significantly increase the likelihood of biopesticide adoption, with training emerging as the strongest determinant, raising adoption probability by approximately 18 percentage points. Each additional year of schooling also increases adoption likelihood by about 2.7 percentage points. Adoption is notably higher among shallot farmers than among those cultivating other crops, reflecting crop-specific vulnerability to pest and disease attacks as well as market quality considerations. These findings underline the importance of integrating behavioral insights into agricultural extension policies through targeted training, farmer field schools, and demonstration programs to strengthen farmers’ capacity and promote biopesticide adoption in support of sustainable agriculture.